Democracy and Reform: Voices in West Asia - RANJIT SAU (Economic and Political Weekly September 18, 2004, 2004)
The US plan for reforms in the Arab world, called the Greater Middle East Initiative, has evoked mixed reactions among Arabs, even as suspicions of US intentions remain widespread. However, the people of the Arab lands are eager for genuine social, political and economic reform, for which there needs to be unity among the people themselves. Arabs could look at the Kerala Jama'at model as a step towards greater solidarity among the peoples of the region.